Invigorasi Larutan Bawang Merah Terhadap Viabilitas dan Vigor Tiga Benih Padi Varietas Lokal - Suparto, Hairu; Sofyan, Antar; Irfan, Muhammad (Jurnal Penelitian UPR, 2023)
Rice production in South Kalimantan during January to September 2020 decreased compared to 2019. The use of rice seeds per hectare  is generally still not in accordance with the recommendations. The local varieties of rice seeds that cultivated are from last year's cropping season, where storage was not good which could lead to a decrease in seed quality. Shallots  contain  hormones auxin and gibberellins, can be used as a natural growth regulator. This study used a solution of shallots on three local varieties of rice seeds. The purpose of this study was to provide information on the use of natural growth regulators in shallot solution as an alternative to increase seed viability to become a provider of quality seeds. This research carried out from October to November 2021 at the Production Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University. The implementation of the research is making shallot stock solution, seed preparation, seed soaking, seed germination, and maintenance. The method used was qualitative using single factor Completely Randomized Design  with three levels of treatment and each treatment consisted of five replications. The results showed that treatment using onion solution invigoration had a significant effects on the parameters of growth uniformity and maximum growth potential of expired local rice seeds of Siam Banjar variety. The highest growth speed and seed germination were found in Siam Saba variety. The highest growth uniformity was found in Siam Unus variety. The highest maximum growth potential is found in  Siam Mutiara variety.